An integrated radiomics nomogram based on conventional ultrasound improves discriminability between fibroadenoma and pure mucinous carcinoma in breast - Wang, Hui; Zha, Hailing; Du, Yu; Li, Cuiying; Zhang, Jiulou; Ye, Xinhua (Frontiers in Oncology, 2023)
Objective: To evaluate the ability of integrated radiomics nomogram based on ultrasound images to distinguish between breast fibroadenoma (FA) and pure mucinous carcinoma (P-MC). Methods: A consecutive of 170 patients with FA or P-MC (120 in training set and 50 in test set) with definite pathological confirmation was retrospectively enrolled. 464 radiomics features were extracted from CUS images and radiomics score (Radscore) was constructed using Least Absolute Shrinkage and Selection Operator (LASSO) algorithm. Different models were developed by support vector machine (SVM), and the diagnostic performance of different models was assessed and validated. Comparison of receiver operating characteristic (ROC) curves,calibration curve and decision curve analysis (DCA) were performed to evaluate the incremental value of the different models. Results: Finally, 11 radiomics features were selected, then Radscore was developed based them，and which was higher of P-MC in both cohorts. In the test group, clinic + CUS + radiomics (Clin + CUS + Radscore) achieved significantly higher area under the curve (AUC) (AUC =0.86, 95%CI, 0.733-0.942) when compared to that of clinic + radiomics (Clin + Radscore) (AUC = 0.76, 95%CI, 0.618-0.869, P> 0.05), clinic + CUS (Clin + CUS) (AUC = 0.76, 95%CI, 0.618-0.869, P < 0.05), Clin ( AUC = 0.74, 95%CI, 0.600-0.854, P < 0.05) , and Radscore (AUC = 0.64, 95%CI, 0.492-0.771, P < 0.05), respectively. The calibration curve and DCA also suggested the excellent clinical value of combined nomogram. Conclusion: The combined Clin + CUS + Radscore model may help improve the differentiation of FA from P-MC.